Multiple-parallel-protease digestion coupled with high-resolution mass spectrometry: an approach towards comprehensive peptide mapping of therapeutic mAbs - Pradhan, Gauri; Sneha, J. M.; Sonwane, Babasaheb P.; Santhakumari, B.; Rao, Alka; Kulkarni, Mahesh J. (Journal of Proteomics, 2021)
Therapeutic monoclonal antibodies (mAbs) are structurally large and complex molecules. To be safe and efficacious, a biosimilar mAb must show high similarity to its reference product in Critical Quality Attributes (CQA). mAbs are highly sensitive to protein expression, production, manufacturing, supply chain, and storage conditions. All these factors make biosimilar mAbs intrinsically susceptible for variability during production. Accordingly, several lots of references and tests are required to establish the biosimilarity of a test mAb. The primary structure is a CQA of a mAb affecting its safety and efficacy. Here, we apply peptide mapping as an analytical method to decipher the primary structure and associated modifications for a quick quality assessment of TrastuzumAb and RituximAb innovator and biosimilar. A multiple-parallel-protease digestion strategy followed by high-resolution mass spectrometric analysis consistently achieved 100% sequence coverage along with reliable detection of post-translational modifications. Additionally, the use of supporting methods such as intact mass analysis and circular dichroism helped us to decipher the primary and higher order structures of these mAbs. We identify discernible variations in the profile of the innovator and biosimilar mAbs and validate the method for quick yet deep comparability analysis of the primary structure of biosimilar mAbs sold in the market. Significance: Peptide mapping using bottom-up approach is one of the most common methods for the characterization of therapeutic monoclonal antibodies. Herein, we describe a multi-parallel-protease digestion strategy using a combination of five different proteases followed by high-resolution mass spectrometric analysis with TrastuzumAb and RituximAb as an example. This resulted in a comprehensive identification of peptides with increased reliability and identification of different PTMs. Additional supporting orthogonal methods like intact mass and higher-order structure analysis helped evaluate broader conformational properties.
Keywords: LC-MS/MS; PTM; RituximAb; Therapeutic monoclonal antibodies; TrastuzumAb

Ultra-high performance liquid chromatography Q-Orbitrap MS/MS-based profiling and quantification of limonoids in Meliaceae plants - Mulani, Fayaj A.; Nandikol, Sharvani S.; Kajjihundi, Jagadeesh S.; Pathappa, Niranjana; Puttappa, Sharanappa; Thulasiram, V. Hirekodathakallu (Analytical and Bioanalytical Chemistry, 2022)
Meliaceae plants have been extensively used in agriculture, folklore, and traditional medicine. They are the major storehouses for structurally diverse limonoids (meliacins) possessing various bioactivities like antifeedant, insecticidal, antimicrobial, etc. However accurate detection of these tetranortriterpenes from the vast pool of metabolites in plant tissue extracts or biological sample is a crucial challenge. Though the mass spectrum (MS) provides the molecular mass and the corresponding elemental composition, it cannot be relied precisely. The exact identification of a specific metabolite demands the MS/MS spectrum containing the signature product ions. In the present study, we have developed the UHPLC Q-Orbitrap-based method for identification, quantification, and characterization of limonoids in different plant tissue extracts requiring minimum plant material. Using this method, we carried out the limonoid profiling in different tissue extracts of sixteen Meliaceae plants and the identification of limonoids was performed by comparing the retention time (RT), ESI-(+)-MS spectrum, and HCD-MS/MS of the purified fifteen limonoids used as reference standards. Our results revealed that early intermediates of the limonoid biosynthetic pathway such as azadiradione, epoxyazadiradione, and gedunin occurred more commonly in Meliaceae plants. The MS/MS spectrum library of the fifteen limonoids generated in this study can be utilized for identification of these limonoids in other plant tissue extracts, botanical fertilizers, agrochemical formulations, and bio pesticides.
Keywords: LC-HRMS; LC-MS/MS; Limonoids; Meliaceae; Natural product; Quantification